Influence of anti‐browning treatments on enzymatic browning, distinctive properties, and microbiological characteristics of banana pulp during short‐term frozen storage. Issue 3 (29th January 2021) - Arora, Simran; Goraya, Rajpreet Kaur; Siddiqui, Saleem; Gehlot, Rakesh
Abstract: Banana pulps (ripe and overripe) were taken to investigate the effectiveness of various anti‐browning agents (0.1 and 0.2% potassium metabisulfite (KMS), 1 and 2% citric acid (CA), 1% ascorbic acid (AA), 1% CA + 0.5% L‐cysteine, 1% CA + 0.5% CaCl2, 1% CA + 1% AA + 0.5% cysteine) to prevent enzymatic browning. Based on the polyphenol oxidase activity, color and sensory attributes, the most effective anti‐browning agent was selected. Results showed that KMS at 0.1% was most effective in inhibiting the browning reaction, which was further used for evaluating the effect of frozen storage (−16°C) for 180 days along with control. But the control sample lasted for 30 days. In ripe pulp: TSS, total and reducing sugars increased, whereas in overripe it decreased during storage but, the pH remained stable. The ascorbic acid, carotenoids, phenols, and color value decreased for both samples slightly during freeze storage. Practical applications: The response of enzymatic browning in banana pulp to different anti‐browning agents is highly variable. In our findings, we found that potassium metabisulfite (KMS) is highly effective in inhibiting (100%) polyphenol oxidase activity. Further, banana pulp stored with KMS treatments showed a slight variation in physicochemical attributes during frozen storage (−16°C) for 180 days. The banana pulp seems to be an important food industrial application by increasing economic value along with waste reduction by minimize losses during postharvest. However, providing the producer an alternative use for converting pulp into various valuable products.